FORMATION OF THE LEVEL OF EMOTIONAL INTELLIGENCE IN ADOLESCENTS WITH DEVIANT BEHAVIOR - Saipova M. V. (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the relationship of emotional intelligence with social behavior, shows the factors influencing the occurrence of addictive behavior in adolescence, reveals the place of emotional intelligence in the prevention of social addictions in adolescents.